Biologics and global burden of asthma: A worldwide portrait and a call for action - Caminati, M.; Morais-Almeida, M.; Bleecker, E.; Ansotegui, I.; Canonica, G.W.; Bovo, C.; Senna, G. (The World Allergy Organization journal, 2021)
Biologics for severe asthma can significantly impact on the burden of disease and also have the potential to reduce asthma mortality. By reviewing the literature and contacting the pharmaceutical companies, the present paper aims at providing a worldwide snapshot of biologic drugs availability, related with the trend of asthma mortality rate, as a marker of the burden of the disease. A decline in the global rate of annual asthma mortality was observed until the 1980s, but overall no further reduction occurred, and the current mortality estimation is 0.19 deaths per 100.000 people. A higher mortality rate has been registered in low and middle-income countries (LMICs), where poor socioeconomic conditions and lack of access to the medical resources are more relevant. The availability of monoclonal antibodies is mainly limited to the developed and high-income countries. Furthermore the overall “asthma management system” in LMICs suffers from a number of restrictions that hamper the widespread availability of biologics besides their costs. The availability of generic drugs in the field of biologics for severe asthma could contribute to facilitate their widespread accessibility. But before that, awareness and expertise regarding severe asthma, and proper tools to assess and manage it, deserve to be shared worldwide. Collaboration projects involving physicians from all the countries through the scientific Academies network and with the support of the Companies active in the field may provide an initial concrete opportunity.